<div>More specifically (assuming I understood the statement correctly):</div><div><br></div><div>Suppose I have two base functors F1 and F2 and folds for each: fold1 :: (F1 a -&gt; a) -&gt; (F1 -&gt; a) and fold2 :: (F2 a -&gt; a) -&gt; (F2 -&gt; a).</div>

<div><br></div><div>Now suppose I have two algebras f :: F1 F2 -&gt; F2 and g :: F2 A -&gt; A.</div><div><br></div><div>When is the composition (fold2 g) . (fold1 f) :: F1 -&gt; A a catamorphism?</div><br><div class="gmail_quote">

On Thu, Aug 23, 2012 at 10:11 PM, Sebastien Zany <span dir="ltr">&lt;<a href="mailto:sebastien@chaoticresearch.com" target="_blank">sebastien@chaoticresearch.com</a>&gt;</span> wrote:<br><blockquote class="gmail_quote" style="margin:0 0 0 .8ex;border-left:1px #ccc solid;padding-left:1ex">

<div>From page 3 of <a href="http://research.microsoft.com/en-us/um/people/emeijer/Papers/meijer94more.pdf" target="_blank">http://research.microsoft.com/en-us/um/people/emeijer/Papers/meijer94more.pdf</a>:</div><div><br>

</div>
<blockquote class="gmail_quote" style="margin:0px 0px 0px 0.8ex;border-left-width:1px;border-left-color:rgb(204,204,204);border-left-style:solid;padding-left:1ex">
it is not true in general that catamorphisms are closed under composition</blockquote><div><br></div><div>When is this true?</div>
</blockquote></div><br>